2007
DOI: 10.1002/jmri.20962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multislice acquisition on T1 and T2 measurements of articular cartilage at 3T

Abstract: Purpose: The aim of this study was to investigate the effect of magnetization transfer on multislice T 1 and T 2 measurements of articular cartilage. Materials and Methods:A set of phantoms with different concentrations of collagen and contrast agent (Gd-DTPA 2-) were used for the in vitro study. A total of 20 healthy knees were used for the in vivo study. T 1 and T 2 measurements were performed using fast-spin-echo inversion-recovery (FSE-IR) sequence and multi-spin-echo (MSE) sequence, respectively, in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
(67 reference statements)
2
30
0
Order By: Relevance
“…[5][6][7]9,[12][13][14][15] In particular, PG content decreases before the loss of denatured collagen, but morphologic changes are not seen in the early stage of osteoarthritis (OA). [4][5][6][7] Although the early denaturalization of articular cartilage can be depicted by T 1 r mapping as well as T 2 mapping and dGEM-RIC, [10][11][12][13][14][15][16] its depiction requires an elongated scanning time. Previous reports in the literature used 4 or 5 diŠerent T 1 r-prepared images with diŠerent TSLs for calculation, which required more than 12 min of scanning time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7]9,[12][13][14][15] In particular, PG content decreases before the loss of denatured collagen, but morphologic changes are not seen in the early stage of osteoarthritis (OA). [4][5][6][7] Although the early denaturalization of articular cartilage can be depicted by T 1 r mapping as well as T 2 mapping and dGEM-RIC, [10][11][12][13][14][15][16] its depiction requires an elongated scanning time. Previous reports in the literature used 4 or 5 diŠerent T 1 r-prepared images with diŠerent TSLs for calculation, which required more than 12 min of scanning time.…”
Section: Discussionmentioning
confidence: 99%
“…2,10 The feasibility of T 1 r mapping in assessing the PG content of articular cartilage has been reported to be the same as that of sodium MR imaging and dGEMRIC. 1,[5][6][7][8][9][10][11][12][13][14][15][16][17] Correlation has been reported between changes in PG content and the T 1 r relaxation time in vitro, 6,9 and in vivo studies have shown the utility of T 1 r mapping for PG changes in articular cartilage, especially for patients with osteoarthritis. [5][6][7]9,12,[13][14][15] However, accurate assessment takes a relatively long time because it requires scan- ning of 4 or 5 diŠerent T 1 r-prepared images with diŠerent times of spin-lock pulse (TSLs), [5][6][7]9,[12][13][14][15] and performance of T 1 r mapping would be preferable with a shorter examination time.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A central issue in the successful development of such therapeutics is the ability to monitor and potentially modify implant properties on an ongoing basis. The application of magnetic resonance imaging (MRI) for visualizing cartilage clinically has been well established, 1,2 while more recently, approaches have been developed to monitor cartilage matrix components in human subjects [3][4][5][6][7][8] and in engineered cartilage constructs. [9][10][11][12][13][14] These latter techniques may be particularly useful for tailoring therapeutic interventions after implantation into a defect.…”
Section: Introductionmentioning
confidence: 99%
“…This is important for the feasibility of quantitative T2 relaxation time measurements in clinical practice. However, potential error sources are introduced by using a MSME spin echo sequence [10][11][12]. A multislice sequence requires sliceselective refocusing pulses.…”
mentioning
confidence: 99%